2006
DOI: 10.3989/gya.2006.v57.i2.32
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of <i>Moringa oleifera</i> seed oil from drought and irrigated regions of Punjab, Pakistan

Abstract: RESUMENCaracterización del aceite de semilla de Moringa oleifera procedente de regiones de secano y de regadío del Punjab paquistaní.La intención del presente estudio ha sido la de investigar la composición del aceite obtenido de la semilla de M. oleifera cultivada en regiones de secano y de regadío Paquistaní. El , respectivamente. Estos resultados ponen de manifiesto que la procedencia de secano es el factor que más visiblemente influyen en el aumento del periodo de inducción y del contenido de C22:0 en lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
72
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 21 publications
20
72
4
4
Order By: Relevance
“…Oleic acid is the principal fatty acid in M.oleifera seed oil and this agrees with values (67.8 -85%) in the literature (Tsaknis et al, 1999;Abdulkarim et al, 2005;Anwar et al, 2006) . Fatty Acid (C ≥16) (%) 99.86 Table 4 shows the classification of the fatty acids in M. oleifera seed oil.…”
Section: Fatty Acid Compositionsupporting
confidence: 79%
See 1 more Smart Citation
“…Oleic acid is the principal fatty acid in M.oleifera seed oil and this agrees with values (67.8 -85%) in the literature (Tsaknis et al, 1999;Abdulkarim et al, 2005;Anwar et al, 2006) . Fatty Acid (C ≥16) (%) 99.86 Table 4 shows the classification of the fatty acids in M. oleifera seed oil.…”
Section: Fatty Acid Compositionsupporting
confidence: 79%
“…Extraction methods reported included mechanical press (Anwar et al, 2006;Eman & Muhamad, 2016), solvent extraction (Anwar & Bhanger, 2003;Abdulkarim et al 2005;Anwar et al, 2006) and enzymatic extraction (Abdulkarim et al 2005;Latif et al, 2011), the yield and physicochemical properties of the oil varied with method of extraction. M. oleifera seed oil has been reported to have high degree of unsaturation with oleic acid (67.8 -85%) as the most prominent fatty acid (Tsaknis et al, 1999;Abdulkarim et al 2005;Anwar et al, 2006;Nzikou et al, 2009). Studies on the viscosity of the oil as a function of temperature (Nzikou et al, 2009) and melting behavior (Mohammed et al, 2003;Abdulkarim et al 2005;Nzikou et al, 2009) of the oil have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid is very important in nervous cell construction; it has fundamental role in cardiovascular diseases prevention (Nasri et al 2005). The high percentage of oleic acid in the oil makes it desirable in terms of nutrition and high stability cooking and frying oil (Anwar et al 2006). A higher intake of oleic acid is associated with decreased risk of coronary heart disease caused by high cholesterol level in blood (Corbett 2003).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…It is widely known that this plant can be utilized for beneficial purposes. Moringa is most often consuming as provisions and remedial resource limited to urban areas [19]. The most recommended coagulating agents with 12-14 kDa mass and about 10-11 isoelectric point (pI) are dimeric cationic proteins.…”
Section: Plant-based Coagulants (Pbc)mentioning
confidence: 99%